Analysis of Speaking Skills with Storytelling Method in Indonesian Language Learning in Elementary Schools - Nidya Chandra Muji Utami; Siti Fatimah Azzahra; Nuryani Nuryani (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
This literature study, entitled "Analysis of Speaking Skills with Storytelling Methods in Indonesian Language Learning in Elementary Schools," describes the literature on speaking skills using the storytelling method with the narrative literature review (NLR) model. The technique employed is the comparison method. The purpose of this study is based on the needs in primary school environments, especially in high school, because knowing the problems and difficulties in applying Indonesian language learning to speaking skills for elementary school students is very much needed. It has been proven that it takes work to maximize students' speaking skills in front of an audience. Researchers identified the subject matter discussed in this study as 40 articles published in national journals within the last ten years. The article Speaking Skills with a Storytelling Approach consists of 20 pieces on speaking skills by various methods, as many as nine pieces for speaking skills in high school, which in general is as much as two articles; additionally, to speak with storytelling skills using a variety of models, as many as four articles; three articles for speaking skills using image media and comics; and the other two articles discuss speaking skills in law school in general. The novelty of the research obtained in the literature review of speaking skills and the theories presented by previous experts The impact of research that uses the study of literature is more significant when other researchers pay attention to the suggestions given by researchers when researching speaking skills.